Pengaruh Kerapatan Vegetasi Terhadap Produktivitas Serasah Hutan Taman Nasional Gunung Leuser - Sri Jayanthi; Zulfan Arico (Elkawnie: Journal of Islamic Science and Technology, 2017)
The research was conducted in January-September 2017 and will continue until December 2017 at Gunung Leuser National Park Resort Tenggulun, Aceh Tamiang District, Aceh Province. The method used to determine the vegetation density is purposive sampling by using a combination of line method and the method of with 20 m x 20 m. For determination of litter productivity by using Litter Trap method, and to analyze physical and chemical content of soil by laboratory test and calculate soil fauna density (biological factor) location determination by using line transect along 100 m, then on every line taken 10 point by method Systematic Sampling is systematically on the 3 (three) research sites that have been determined. Based on the research results for the highest density of tree vegetation found in plot 4 with the absolute density of 175 Ind/ ha this is in line with the highest litter productivity value also found at high density (plot 4) which is 14,5 gr/m2/week. Physical chemical factors are found in high density of air temperature 26 0C, humidity 80 %, soil temperature 25 0C, light intensity 118 Candella, soil pH 5.6, C-Organic 4.80 %, N-Total 0.55%, C/N of 4,24 %, P-Bray 23,03 ppm and K-tukar 0,41 Me/100.